The executive statutes of the investment guarantees and incentives اللائحة التنفيذية لقانون ضمانات وحوافز الاستثمار رقم 8 لسنة 1997 - Egypt; The middle east library for economic services, translator. (2025)
Part-1 Conditions and limits of investment fields. Part-2 Founding the companies Chapter 1 Companies the activities of which are confined to the fields prescribed in the article (1). Chapter 2 Multi-purpose and activity companies. 24 Part-3: Individual firms. 25 Part-4: Investment and licenses services. Part-5: Workers' participation in the management of joint-stock Companies.IE Part-6: Automatic tax exemption. 33 Part-7: Appropriation of lands. Part-8: Free zones.